2011
DOI: 10.1007/s11284-011-0883-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative estimation of insect diversity inhabitingCalotropis procerain industrial and nonindustrial areas of West Bengal, India

Abstract: This paper compares the species richnesses, Bray-Curtis similarities, species diversities, evennesses, and the results of various analyses (multivariate, logarithmic series, and lognormal distribution analyses) of insects from four orders (viz., Hemiptera, Orthoptera, aculeate Hymenoptera, and Coleoptera) inhabiting a medicinal plant, Calotropis procera among eight sites within industrial and nonindustrial zones in the Purba Medinipur district (erstwhile Midnapore), West Bengal, India. Both cluster analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The insects collected from C. gigantea during this study in Sri Lanka are very similar to the insects reported on C. procera and C. gigantea from India (Pugalenthi and Livingstone, 1997;Chandra et al, 2011;Jana et al, 2012;Dhileepan 2014). A similar study had been conducted in Saudi Arabia related to C. procera and 99 insect species belonging to 43 families were identified (Al dhafer et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The insects collected from C. gigantea during this study in Sri Lanka are very similar to the insects reported on C. procera and C. gigantea from India (Pugalenthi and Livingstone, 1997;Chandra et al, 2011;Jana et al, 2012;Dhileepan 2014). A similar study had been conducted in Saudi Arabia related to C. procera and 99 insect species belonging to 43 families were identified (Al dhafer et al, 2011).…”
Section: Discussionsupporting
confidence: 82%
“…Wijeweera et al 125 (Chandra et al, 2011), 8 species of insects from 6 families have been documented on C. procera. Similarly, a study in West Bengal in India reported 19 insect species from ten families of C. procera (Jana et al, 2012).…”
Section: Discussionmentioning
confidence: 94%